All‐trans retinoic acid induces leukemia resistance to NK cell cytotoxicity by down‐regulating B7‐H6 expression via c‐Myc signaling. Issue 1 (1st January 2021) - Cao, Guoshuai; Cheng, Ying; Zheng, Xiaodong; Wei, Haiming; Tian, Zhigang; Sun, Rui; Sun, Haoyu
Abstract: Background: The interaction between activating receptor NKp30 and its major tumor ligand B7‐H6 is important for NK cell‐mediated tumor rejection. However, the regulation of B7‐H6 by tumor therapeutics remains largely unknown. In this study, we investigated the regulation of B7‐H6 by all‐trans retinoic acid (atRA), a terminal differentiation inducer of tumor cells that is extensively used for clinical leukemia therapy. Methods: We investigated the role of NKp30:B7‐H6 axis in NK cell‐mediated tumor lysis against leukemia cells and the influence of atRA treatment on the cytotoxicity of NK cells using NK cell lines (NK92 and NKG) and leukemia cell lines (U‐937 and THP‐1). We evaluated the effect of atRA treatment on the expression of B7‐H6 using real‐time PCR, flow cytometry and western blotting. We used CRISPR/Cas9 to knockdown B7‐H6 expression and siRNA to knockdown c‐Myc in U‐937 cells to evaluate the role of B7‐H6 and c‐Myc in atRA‐induced tumor resistance against NK cells. Results: NK cell‐mediated U‐937 cell lysis was mainly dependent on NKp30/B7‐H6 interaction. Blockade of B7‐H6 by monoclonal antibody significantly impaired NK cytotoxicity. atRA treatment induced U‐937 resistance to NK cell cytotoxicity by reducing B7‐H6 expression, and showed no effect on NK cytotoxicity against B7‐H6 knockdown U‐937 cells. Epigenetic modifications, such as DNA methylation and histone deacetylase (HDAC), were not responsible for atRA‐mediated B7‐H6 down‐regulation as inhibitors of these pathways could not restore B7‐H6 mRNA expression. On the other hand, atRA treatment reduced c‐Myc expression, which in turn inhibited the transcription of B7‐H6 on leukemia cells. Conclusion: atRA treatment promotes tumor cell resistance against NK cell‐mediated lysis by down‐regulating B7‐H6 expression via the c‐Myc signaling pathway, suggesting that more attention needs to be paid to the immunological adverse effects in the clinical use of atRA treatment.